Mental Health Problems in Nepalese Migrant Workers and their Families - Mahat, Pashupati; Thorley, Kevan; Kunwar, Karuna; Ghimire, Smriti (Journal of BP Koirala Institute of Health Sciences, 2021)
In this cross-sectional study, we aimed to describe the mental health problems of Nepalese migrant workers and their family members at home in Nepal. Families of migrant workers left behind in Nepal from nine project districts were interviewed to assess the psychosocial problems and offered appropriate psychosocial counselling. We assessed 747 individual members. Ninety-five returned migrant workers received psychosocial counselling, 67% of whom were male. The majority (56%) of the returnees suffered from anxiety, 23% had depression and 11% had serious mental illness. The left-behind family members amounted to 653, 93% of whom were female. The majority (56%) had anxiety, 26% had depression, 7% expressed suicidal ideation or had attempted suicide, 2% had severe mental illness. We concluded that majority of returning workers and left behind family members suffered from anxiety and depression.